Influences of Soil Water Content and Porosity on Lightning Electromagnetic Fields and Lightning-Induced Voltages on Overhead Lines - Liu, Yinping; Jiang, Yuhui; Gao, Qisen; Li, Xia; Yang, Gan; Zhang, Qilin; Tang, Bo (Frontiers in Environmental Science, 2022)
This study is performed to analyze the effects of both soil water content and porosity, two of the influencing factors of the finite conductivity, on the propagation of lightning electromagnetic fields (LEMFs) and lightning-induced voltages (LIVs) on overhead lines. A two-dimensional finite difference time domain (FDTD) model together with an improved Archie’s soil model is adopted for the field calculation at close distances from the lightning channel. The obtained results confirm that the soil water content and porosity have notable impacts on the peak values of LEMFs, especially the horizontal electric field. Moreover, the soil water content and porosity are correlated when acting together. The peak values of the horizontal electric field are found to be markedly influenced by the porosity changes at high water content or the water content changes at low porosity. The LIVs on overhead lines in these two cases are also studied. There appear to be greater differences in the induced voltages as the water content changes at low porosity.